A detailed study of the combustion-fuel behavior of nanofuels containing boron/catalyst nanohybrid particles - Kucukosman, Ridvan; Yontar, Ahmet Alper; Agbulut, Umit; Unlu, Cumhur Gokhan; Ocakoglu, Kasim (ELSEVIER SCI LTD, 2025)
Boron, with its high theoretical calorific value, is a promising alternative fuel, but its problematic oxidation behavior prevents complete combustion and limits its potential. This study focuses on the production of amorphous boron (AB) particles with reduced B2O3 layers using ball milling and their decorating with perovskite-type nano catalysts (La0.7 Nd0.3MnO3, Nd0. 7Ba0.3MnO3, La0.5 Nd0.3Ba0.2MnO3) by a cost-effective ultrasonication methods. The structural characterizations of all particles were characterized by SEM and XRD techniques. To evaluate the catalytic activity of the nanocatalysts, elemental analysis and surface area measurements were carried out by XPS and BET analysis, respectively. Combustion tests on gasoline-based nanofuels (2.5 and 7.5 wt %) in a controlled droplet-scale chamber showed that higher particle concentrations reduced ignition delay. However, boron hybrid particles had ignition delays similar to pure boron particles. Residual aggregate temperatures of 7.5 wt% AB-LNM1, AB-NBM, and AB-LNBM1 droplets were 111.5 %, 100 %, and 110.4 % higher than those with AB-BM. SEM-EDX analyses of residues revealed that AB-LNBM1 hybrids had the highest catalytic efficiency, with 5.47 % carbon and 17.53 % oxygen, significantly improving boron and soot oxidation. Engine tests using 250 ppm diesel blends highlighted NBM nanoparticles as having the lowest BSFC, while AB-LNBM1 achieved the highest HRR increase (12.69 %) and CO2 emissions (9.53 %) at 60 Nm. AB-LNBM1 also reduced HC emissions by 53.33 % at 15 Nm, and NBM provided the largest NOx reduction (9.70 %) at 30 Nm. Overall, boron/ catalyst nanohybrids enhanced combustion behavior, improved fuel efficiency, and reduced pollutant emissions. These findings suggest that such hybrids have significant potential for advancing alternative fuel applications and reducing the environmental impact of hydrocarbon fuels.
Keywords: Boron; Perovskites; Combustion catalysts; Gasoline; Diesel; DROPLET; PEROVSKITE; REDUCTION; CATALYSTS; IGNITION; NANOPARTICLES; PERFORMANCE; OXYGEN; SOOT; Energy & Fuels; Engineering